A framework design for optimizing scaffolding erection by applying mathematical models and virtual simulation - Hou, L.; Wu, Changzhi; Wang, X.; Wang, J. (American Society of Civil Engineers (ASCE), 2014)
© ASCE 2014. Temporary structures, like scaffolding, have a significant impact on the quality, safety and profitability of construction projects. Workplace Health and Safety (WHS) Authorities in Australia have found that 40% of all scaffolding projects do not comply with national safety and design standards. Thereby, the practical guidance in scaffolding cases should be treated as a critical research focal point in conjunction with the general Australia-wide Occupational Safety and Health (OSH) requirements, acts and regulations. At present, limited research attention has been placed on the impact of design and validation of scaffolding erection and dismantling on OSH, especially considering working at height. To address this issue, the aim of this paper is to: (1) develop a framework of mathematical optimization algorithms for scheming the scaffolding erection and dismantling during the planning process, and (2) explore how to combine the mathematical methods to produce a good solution in a relatively short time by taking consideration of special characteristics and complications of scaffolding. The framework can resolve the relatively multi-objective optimization issues and produce the optimal solutions with higher complexity. In parallel, virtual simulation scenario to digitalize the optimized work schemes of scaffolding is also proposed within the framework. In this sense, several sources of risks in scaffolding erection and dismantling - including: (1) work area design and lay-out (e.g., inadequate space for task type); (2) the nature of equipment or tool; and (3) erection and dismantling sequences load and working environment - will be comprehensively optimized and visually simulated. It is envisaged that this integrated framework that combines the mathematical algorithms and virtual representation might, for the first time, automate the most effective way of controlling the risks in the context of scaffolding practice.